Attitudes towards carbon taxes across Europe: The role of perceived uncertainty and self-interest. (May 2020) - Umit, Resul; Schaffer, Lena Maria
Abstract: While using carbon taxes to reduce greenhouse gas emissions may well be effective, this has recently proved too unpopular to put into practice in a number of countries. Yet, at a time when governments across the world are preparing their nationally determined contributions to the Paris Agreement, our knowledge of whether and why people oppose these taxes originates from a single or small number of cases. Drawing on the European Social Survey (n = 44, 387), this article provides evidence on public attitudes towards increasing taxes on fossil fuels to reduce climate change from 23 countries, most of which have never featured in the literature before. The results point to a widespread aversion to carbon taxes. On the one hand, this worsens with the perceived costs of taxes, such as the case among consumers who depend highly on energy. On the other, it improves with political trust and external political efficacy—factors that help ease the uncertainty around policy proposals. Our estimations suggest that the effect of changes in these factors alone would be large enough to reverse the public resistance to carbon taxes in some countries. These results are robust to a number of alternative specifications and various checks. Highlights: This is a study of public attitudes towards carbon taxes across 23 countries. There is no public support for carbon taxes in most countries. Support is lower among groups with high-energy dependence. Support increases with political trust and efficacy.